Analisis gaya dan daya pada alat pengaduk mesin kristalisasi jahe dengan kapasitas 5 kg/jam - Fatkur Rhohman; Pramesti, Yasinta Sindy; Setyowidodo, Irwan; Ilham, M. Muslimin (Jurnal Mesin Nusantara, 2023)
Red ginger is a plant that is easy to grow in Indonesia and is well known as a spice plant and can be found in many plantation farmers, such as in Kediri Regency, Kepung District, Besowo Village. One of the preparations of red ginger that local residents are involved in is making instant herbal medicine. The processing of instant herbal medicine with red ginger as raw material includes the process of washing, grating, squeezing, and cooking so that the final result is crystallized red ginger. The focus of discussion in this article is the mixing process. The design of this mixing machine uses a power of 0.5 HP and a rotation of 1400 rpm to mix 5 kg/hour of red ginger dough. This stirring process takes 60 to 80 minutes until red ginger crystals form.